Experience of social discrimination correlates with neurometabolism: a pilot study in heroin addicts - Frischknecht, Ulrich; Hermann, Derik; Heinrich, Milena; Hoerst, Mareen; Weber-Fahr, Wolfgang; Vollstädt-Klein, Sabine; Kiefer, Falk; Mann, Karl; Ende, Gabriele (European archives of psychiatry and clinical neuroscience, 2013)
Experimental social neuroscience has shown that being socially excluded is processed in the anterior cingulate cortex (ACC). We hypothesize that a chronic form of social exclusion resembling one aspect of social stigmatization is associated with altered neural plasticity reflected by neurometabolic alterations in the ACC. To test this hypothesis, a highly stigmatized patient group of heroin addicts (N = 15) during opiate maintenance therapy rated a questionnaire about being stigmatized, and neurometabolic markers in the ACC were determined using 1H MR spectroscopy. We found a negative correlation between discrimination experience and N-acetylaspartate (NAA), indicating attenuated neuron functioning in the anterior cingulate cortex in those patients reporting high discrimination experience. Furthermore, perceived stigmatization showed an association with anxiety that was mediated by NAA. Although the correlative analysis cannot give evidence for a causal relationship, the relation of NAA in the ACC and discrimination experience indicates a malfunction of the neural system involved in cognitive control over emotionally relevant social stimuli in discrimination reporting heroin addicts. Further research is needed to elucidate factors associated with chronic stigmatization.